Record of the rare Caribbean mud eel, Pythonichthys sanguineus (Heterenchelyidae, Anguilliformes), in the region of the Amazon Reef - Rotundo, Matheus Marcos; Machado, Leonardo; Oliveira, Claudio; Santos, Wagner César Rosa Dos; Marceniuk, Alexandre Pires (Instituto Nacional de Pesquisas da Amazônia, 2019)
ABSTRACT As they spend most of their time buried in the substrate and are not a fishery resource, heterenchelyids are seldom seen. These eels are characterized by their greatly reduced eyes, which are covered by semi-transparent skin, the absence of a pectoral fin or lateral line, and no pores on the head or body. Pythonichthys sanguineus is a particularly poorly-known species, with only eight scientific records from Cuba, Puerto Rico, Colombia, Venezuela, Guyana, and Suriname. The present study is based on six adult specimens of P. sanguineus captured by vessels of the shrimp trawling fleet along the northern Brazilian coast, in the vicinity of the Amazon Reef. We provide meristic, morphometric and DNA barcoding data. These findings provide insights into the distribution of the species off the northern Brazilian coast and contribute to the discussion about the southern limit of the Greater Caribbean fauna.

RESUMO Heterenchelídeos passam a maior parte do tempo enterrados no substrato e raramente são vistos, não representando recursos pesqueiros importantes. Essas enguias são caracterizadas por seus olhos muito reduzidos e cobertos por pele semi-transparente, ausência de nadadeiras peitorais ou linha lateral, e ausência de poros na cabeça ou no corpo. Pythonichthys sanguineus é uma espécie particularmente pouco conhecida, com apenas oito registros em coleção zoológica para Cuba, Porto Rico, Colômbia, Venezuela, Guiana e Suriname. O presente estudo é baseado em seis espécimes adultos de P. sanguineus capturados pela frota industrial de arrasto de camarão-rosa na costa norte do Brasil, ao largo dos Recifes da Amazônia. Apresentamos dados merísticos, morfométricos e de DNA barcoding dos exemplares examinados. O registro fornece informações importantes sobre a distribuição da espécie na costa norte do Brasil, e contribui para a discussão sobre o limite sul da fauna do Grande Caribe.
Registro da rara enguia de lama do Caribe, Pythonichthys sanguineus (Heterenchelyidae, Anguilliformes) na região dos Recifes da Amazônia
Keywords: fisheries; conservation; Brazilian northern coast; new record; systematics; pesca; conservação; costa norte do Brasil; novo registro; sistemática